2019
DOI: 10.1093/annonc/mdy524
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes (PROs) as a routine measure for cancer inpatients: the final missing piece of the puzzle?

Abstract: The Thoraco-Pulmonary Medical Oncology is supported by Associazione Italiana per la Ricerca sul Cancro (AIRC) (no grant number applies). Disclosure Alessandro Morabito received honoraria from AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Merck Sharp & Dohme, Pfizer and Roche. 'Who better than the patient to tell you whether the services we provide supply value or not?' (Carolyn Kerrigan)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Clinicians have reported that PRO measures are useful in assessing patients' views regarding changes in their health status and prompting difficult and sensitive conversations about topics, such as depression, anxiety, and suicidal ideation [23][24][25]. Furthermore, a previous study reported that compared to patients with cancer in the usual care group, those in the intervention group using PROs as routine measure experienced more days with lower psychological stress [26].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have reported that PRO measures are useful in assessing patients' views regarding changes in their health status and prompting difficult and sensitive conversations about topics, such as depression, anxiety, and suicidal ideation [23][24][25]. Furthermore, a previous study reported that compared to patients with cancer in the usual care group, those in the intervention group using PROs as routine measure experienced more days with lower psychological stress [26].…”
Section: Discussionmentioning
confidence: 99%
“…PROMs are one way to support such relationships by assessing the nature and severity of the physical, psychosocial and functional disabilities [ 13 , 14 ] which patients may encounter during and/or over time with a disease [ 10 , 13 ]. The identification of such disabilities can lead to alleviation of the burdens caused by the illness or its treatment [ 4 , 15 ]. Ultimately, the use of PROMs may help improve the quality of life for patients diagnosed with haematological disorders [ 4 , 13 , 16 ], who are a heterogeneous and challenging population.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of patient-reported outcome measures (PROMs) in cancer care shows promising results, especially within clinical care [25], [26], [27]. Thus, one way to complement cancer registrations could be to routinely collect PROMs at specific time points [26], [28].…”
Section: Interpretation and Implicationsmentioning
confidence: 99%
“…Under 40 (0,4) 0 (0,0) 40-49 (7,8) 381 (8,5) <0.001 50-59 (17,3) 941 (20,9) 60-69 (28,8) 1550 (34,4) 70-79 (28,4) 1168 (25,9) (22,9) 1186 (26,3) III (20,0) 1114 (24,7) IV (20,6) 527 (11,7) Missing (6,7) 177 (3,9) Analysis of milestone dates 27) 54 ( 24) 89 ( 32) 56 ( 22) 76 ( 37) 47 ( 29) 65 ( 31) 22 ( 28) High 1 (0.6) 1 ( 1) 4 ( 1) 3 ( 1) 0 (0) 0 (0) 2 ( 1) 0 (0) Missing 0 (0) 1 ( 1) 1 ( 1) 1 ( 1) 0(0) 7 ( 4) 0 (0) 0 (0) 4) 7 ( 4) 1 ( 1 54) 73 ( 53) 78 ( 55) 93 ( 60) 51 (…”
Section: Fundingunclassified